Bonds and Dutch auction - Pacheco Mexzon, Raimundo (2015)
When a company issues bonds to financed can use Dutch Auction to place these securities in the capital market. Therefore it is objective of this article, indicate how is applied the Dutch Auction to place the bonds to investors participating in the public offering.